FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN LABA DAN DAMPAKNYA TERHADAP PERTUMBUHAN ASET LPD DI KABUPATEN GIANYAR - Lestari Dewi, Ni Made Jeny; Suartana, I Wayan (E-Jurnal Akuntansi, 2017)
The profit growth was an increase in profit or reduction earnings in certain periods expressed percentages. Asset growth is the variable that reflects the size of a company. This study uses five factors to affect profit growth as well as the impact on asset growth is the level of cash turnover, credit growth rate, the growth rate of savings, interest expense growth rate, and the growth rate of labor costs. This study aims to determine the analysis of the factors-factors that affect earnings growth and impact on asset growth LPD. This research was conducted at LPD in Gianyar regency. The number of samples obtained as many as 162 samples by purposive sampling method. Data collection methods is documentation, while the data analysis technique used is multiple linear regression analysis. The results showed that the variable rate cash turnover, credit growth, deposit growth, and labor costs petumbuhan effect on earnings growth.
Keywords: LPD, Profit Growth, Asset Growth